LEGAL ASPECTS OF DIGITALIZATION IN LAND REGISTRATION - Risky Andes Syaputra (International Peneliti Ekonomi, Sosial dan Teknologi, 2022)
In order to carry out land registration, it is necessary to have an institution that serves affairs related to land, the institution in question is the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (Ministry of ATR/BPN). The research used isnormative legal research, namely research conducted by reviewing the laws and regulations that apply or are applied to a particular legal problem. Legal sources in this study include primary legal sources obtained from legislation and other regulations related to research problems and secondary legal sources obtained from law books, journals and other scientific works related to research. From the results of the research, it is concluded that the regulation of digital services in land registration is currently only regulated in part or separately from regulations related to information technology and land registration regulations. The regulations for digital land registration services have not been specifically regulated in one regulation, even though computerized services and service innovations with digital systems in land services have been implemented. The impact of this digital service can be related to the protection and legal certainty of the community for their land rights, so the digital land registration service must be regulated in a complete regulation, so that the community is not harmed. The procedure for implementing digital registration is not in accordance with the land registration regulations, as well as the protection of employees who provide these services is not regulated in special regulations so that currently in addition to digital services with KKP the service process and manual data at the Land Office are still in use, the problem is if there are Differences in data between digital and manual data that are not known by implementing employees will cause fatal errors, so it can be said that the digital registration service process has not fully guaranteed legal certainty and protection.